Disruptive Effects of Vigilance on Dominant Group Members' Treatment of Outgroup Members Choking Versus Shining Under Pressure. [article]. - Vorauer, Jacquie D.
Three studies examined the hypothesis that evaluative concerns exert a disruptive effect on intimacy-building behaviors by dominant group members in intergroup interaction. The authors predicted that although evaluative concerns would lead individuals with negative baseline response to outgroup members to shine (i, e., to exhibit warmer, more friendly behavior), such concerns would have a contrary, choking, effect on individuals with a more positive baseline response. Results were generally consistent with these hypotheses across 3 different operalizations of evaluative concerns and regardless of whether individuals orientation toward outgroup members was assessed in terms of prejudiced racial attitudes or racialmingroup identification. Implications for lower status group members' experience of intergroup reaction and for the prejudice-reduction process are considered. (from the author)